2015
DOI: 10.1017/s1047951115000426
|View full text |Cite
|
Sign up to set email alerts
|

Does functional health status predict health-related quality of life in children after Fontan operation?

Abstract: Medical history and worse present medical status not only predicted worse physical parent-reported and self-reported health-related quality of life but also worse psychosocial health-related quality of life and subjective cognitive functioning. These findings will help in identifying patients who are at risk for developing impaired health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
(84 reference statements)
0
27
1
Order By: Relevance
“…In fact, any physical limitation could invalidate both physical and psychological aspects. 40 In our study population, the mean score of every category of the SF-36 showed no relevant difference in comparison to the expected scores of a healthy comparison group. As explanation to such high scores, it has been suggested that the patients cope with their pathology and express their feelings more realistic than their peers, a fact that is already known from childhood oncology patients.…”
Section: Discussionmentioning
confidence: 45%
“…In fact, any physical limitation could invalidate both physical and psychological aspects. 40 In our study population, the mean score of every category of the SF-36 showed no relevant difference in comparison to the expected scores of a healthy comparison group. As explanation to such high scores, it has been suggested that the patients cope with their pathology and express their feelings more realistic than their peers, a fact that is already known from childhood oncology patients.…”
Section: Discussionmentioning
confidence: 45%
“…Patients with Fontan circulation might experience an affected quality of life (37). Studies have reported a negatively affected quality of life (37)(38)(39)(40)(41)(42)(43) and reduced exercise performance even in patients without severe complications during surgical procedures and medical follow-ups (23,25,26,30). Also, it has been shown that patients with Fontan circulation have a lower quality of life compared with patients with less severe heart defects (38).…”
Section: Long-term Outcomementioning
confidence: 99%
“…In a recent study (24), it was shown that patients with Fontan circulation had decreased physical performance, but similar quality of life compared with healthy subjects. Atz et al 44 health-related quality of life (37). A clinical problem, raised by patients and their parents, is disturbed sleep and daily fatigue.…”
Section: Long-term Outcomementioning
confidence: 99%
“…of pumping ventricle, number of surgical procedures and complications, age at completed Fontan circulation and arrhythmia have also been reported to influence healthrelated quality of life (11). To our knowledge, there are no available reports on the daily participation in physical exercise and sports among young Fontan patients and how exercise is perceived.…”
Section: Key Notesmentioning
confidence: 99%
“…The quality of life for children with severe cardiovascular disease has been shown to be lower than that of healthy children . In Fontan patients, factors such as the type of pumping ventricle, number of surgical procedures and complications, age at completed Fontan circulation and arrhythmia have also been reported to influence health‐related quality of life . To our knowledge, there are no available reports on the daily participation in physical exercise and sports among young Fontan patients and how exercise is perceived.…”
Section: Introductionmentioning
confidence: 99%